Efectos de diferentes dosis de citoquinina en interacción con un compuesto orgánico en la germinación in vitro de semilla de moringa moringa oleifera lam - Figueroa Vera, Ronny Frank (2015)
In the Laboratory of Biotechnology, Academic Unit of Agricultural Sciences at Universidad Técnica de Machala was experimented with culture media supplemented with phytoregulators used in in vitro processes, in order to achieve high levels of germination and development of Moringa seeds, considering the following objectives: 1. Establish the effects of BAP and coconut water on germination and in vitro development of Moringa seed. 2. Determine the concentration of the organic composite that interacts better with the cytokinin. The genetic material that was used Moringa seeds were collected from the Granja Sta. Ines. Factors study were three levels of BAP 0.10, 0.25 and 0.50 mg/l and three doses of coconut water 100, 150 and 200 ml/l, besides the control without phytoregulators, counting of 10 treatments. The variables evaluated were, pollution and germination percentage, days to germination, root number, root length, seedling height and number of leaves. The selected seeds were taken by their physiological state, after washing the seed coat was removed and immersed in 70% alcohol for 30 seconds, then sodium hypochlorite 1% for 10 minutes. Sowing seeds was performed in glass jars with Murashige and Skoog medium supplemented with BAP and coconut water. They were incubated at 25 ± 2 ° C, relative humidity 75%, 1500 lux and a photoperiod of 16/8 h light/dark, with assessments every two weeks. For statistical analysis was used the mathematical model completely randomized with 10 seeds per treatment, and a total of 100 container. The results obtained in the investigation yielded statistical significance for the variables; number and root length, seedling height and leaf number at certain stages of evaluation. Treatments with BAP and coconut water work by stimulating cell division in similar way that natural cytokinins. The issuance of roots and leaves of Moringa seedlings, followed a linear regression model achieved high growth rate. The best interaction between BAP and coconut water, it is gave on the treatment T2 0.1 mg/l BAP - 150 cc/l coconut water.